2020
DOI: 10.1017/s0021859620000210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal vitamin D3 during pregnancy on FASN and LIPE mRNA expression in offspring pigs

Abstract: In this study, sows were fed 200 (LD), 800 (ND) and 3200 (HD) IU of vitamin D3/kg basal diet during pregnancy (from 41 d to birth), respectively. All their offspring pigs were fed the same vitamin D3 replete die. At 150 days of age, a total of 18 offspring pigs (six offspring pigs per maternal diet group, sex balance) were weighed and slaughtered to investigate effects of maternal vitamin D3 during pregnancy on fatty acids synthase (FASN) and hormone-sensitive lipase (LIPE) expression in offspring pigs. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It was previously demonstrated that shear force is negatively correlated to IMF content of muscle (Magnabosco et al, 2016). In this study, shear force in offspring pigs from LD group were significantly higher than that from HD group, which suggested that maternal vitamin D 3 deficiency may decreased the tenderness of longissimus dorsi muscle in offspring pigs during frozen storage through inhibiting the formation of IMF (Guo et al, 2020b). These results indicated that maternal vitamin D 3 status could affect the meat quality attributes in offspring pigs during frozen storage.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…It was previously demonstrated that shear force is negatively correlated to IMF content of muscle (Magnabosco et al, 2016). In this study, shear force in offspring pigs from LD group were significantly higher than that from HD group, which suggested that maternal vitamin D 3 deficiency may decreased the tenderness of longissimus dorsi muscle in offspring pigs during frozen storage through inhibiting the formation of IMF (Guo et al, 2020b). These results indicated that maternal vitamin D 3 status could affect the meat quality attributes in offspring pigs during frozen storage.…”
Section: Discussionmentioning
confidence: 51%
“…At day 150 of offspring age, longissimus dorsi muscle samples were collected within 24 h after slaughtering. Animal diets, feeding trait and slaughter methods are consistent with our previous study (Guo et al, 2020a;Guo et al, 2020b). Samples preparation of porcine longissimus dorsi muscles were according to previous reports (Zhang et al, 2019).…”
Section: Samples Preparationmentioning
confidence: 61%
See 1 more Smart Citation
“…Simultaneously, flame‐retardant PVA‐based materials have become a significant research hot spot because of its structure and performance advantages in aerogels. Montmorillonite (MMT), [ 19 ] clay, [ 20 ] hydroxyapatite, [ 21 ] and gelatin [ 22 ] are commonly used fillers for preparing flame retardant PVA aerogels. Chen's research group [ 23 ] reported four kinds of flame retardant PVA aerogels, specifically, PVA/SiO 2 , PVA/halloysite, PVA/MMT, and PVA/laponite.…”
Section: Introductionmentioning
confidence: 99%
“…In the lipid metabolism, vitamin D has potential nutritional regulation in animals (Wang et al, 2016). Maternal vitamin D 3 levels affected intramuscular adipocyte commitment and differentiation in piglets by regulating adipogenesis related genes expression (Guo et al, 2020a). Maternal vitamin D deficiency during pregnancy promoted the proliferation and differentiation of pre-adipocytes, and resulted in offspring obesity (Wen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%